2022
DOI: 10.1002/ecs2.4233
|View full text |Cite
|
Sign up to set email alerts
|

Loss of riparian forests from wildfire led to increased stream temperatures in summer, yet salmonid fish persisted

Abstract: Native salmonid fishes-cutthroat trout (Oncorhynchus clarkii) and steelhead/rainbow trout (Oncorhynchus mykiss)-are ecologically, culturally, and economically important species distributed across western North America. These fish are generally considered "cold-water" adapted species. As such, recent studies have speculated about the potential effects of climate change on these native salmonids if stream temperature thresholds exceed 16-20 C during the summer. However, the magnitude of stream thermal responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…(2014) observed that trout in the burned sites were consuming smaller and less prey than fish in reference sites, which along with increased water temperatures resulted in bioenergetically stressful conditions and decreases in fish biomass. Indeed, all six studies in this review that reported fish length observed an increase in burned sites, which are likely related to warmer water temperatures that lead to faster growth, which in turn can exacerbate competition for limited food resources and lead to lower lipid content (Rosenberger et al., 2015) or lower fish condition (Warren et al., 2022). Regarding riparian predators, two out of four studies reported an increase in the emergence of insects in sites that burned several years ago, which could partly explain the greater density of spiders observed in burned sites in two out of four studies, as well as the greater bat echolocation reported by one study (Harris et al., 2018; Malison & Baxter, 2010; Mellon et al., 2008).…”
Section: Discussionmentioning
confidence: 96%
“…(2014) observed that trout in the burned sites were consuming smaller and less prey than fish in reference sites, which along with increased water temperatures resulted in bioenergetically stressful conditions and decreases in fish biomass. Indeed, all six studies in this review that reported fish length observed an increase in burned sites, which are likely related to warmer water temperatures that lead to faster growth, which in turn can exacerbate competition for limited food resources and lead to lower lipid content (Rosenberger et al., 2015) or lower fish condition (Warren et al., 2022). Regarding riparian predators, two out of four studies reported an increase in the emergence of insects in sites that burned several years ago, which could partly explain the greater density of spiders observed in burned sites in two out of four studies, as well as the greater bat echolocation reported by one study (Harris et al., 2018; Malison & Baxter, 2010; Mellon et al., 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Although we have a strong understanding of the direct effects of temperature on physiology under controlled laboratory conditions, many factors including food availability, may modify outcomes and lead to unexpected changes in river ecosystems (Solokas et al, 2023; Warren et al, 2022). Therefore, past research conducted under controlled, experimental conditions may not reflect actual responses to climate change because of the complex interactions between organisms, resource availability, and environments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high pH exposure and subsequent rise in blood pH e reduce [H + ] and hinders the process of ammonia excretion as increased proportion of gaseous NH 3 (compared to ionic NH 4 + ) in the environment slows the outward diffusion of NH 3 as well as net total ammonia excretion rate, which ultimately results in a rapid rise in blood total ammonia (Wilkie and Wood, 1991, 1996; Wilkie et al, 1993). The alkalosis-induced disruption to ammonia excretion is likely further aggravated by increased ambient temperature typical of aquatic systems after the wildfire denudes the overhead shading vegetation in riparian habitats (Warren et al, 2022), and this trend is observed in the majority of studies (Paul et al, 2022). Warmer temperature would inevitably elevate basal metabolic demands, increases organismal metabolism, promote faster ammonia production, and decrease the energy budget available for mitigating the IOA-B disturbance (Gomez Isaza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%